Application of a hybrid large-particle method for calculating multicomponent gas mixture flows - Sadin, D.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2020)
This paper is devoted to a generalization of a hybrid large-particle method for the numerical simulation of multicomponent gas mixture flows in the presence of gas interfaces with various thermodynamic properties. The method belongs to the class of shock-capturing and interface-capturing algorithms. The employed difference scheme is conservative and uniform and possesses the second order approximation in space and time on smooth solutions. The obtained numerical results show the efficiency of the method in a wide range of Mach numbers and ratios of gas dynamic parameters. The error analysis performed near the contact discontinuities on grids of various resolutions confirms the convergence of numerical results to the self-similar solutions.